Bayesian analysis of three parameter absolute continuous Marshall–Olkin bivariate Pareto distribution. Issue 2 (3rd April 2018) - Paul, Biplab; Dey, Arabin Kumar; Kundu, Debasis
ABSTRACT: This paper provides Bayesian analysis of absolute continuous Marshall–Olkin bivariate Pareto distribution. We consider only three parameters for this Marshall–Olkin bivariate Pareto distribution. We take two types of prior—reference prior and gamma prior for our analysis. Bayesian estimate of the parameters are calculated based on slice cum Gibbs sampler and Lindley approximation. Credible intervals are also provided for all methods and all prior distributions. A real-life data analysis is shown for illustrative purpose.